Analisis Faktor Yang Mempengaruhi Minat Penggunaan Aplikasi Indrive Menggunakan Model UTAUT2 - Grace Martian Hakim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study analyzes the interest in using the Indrive application in Bandung using the UTAUT2 Model. The purpose of this study is to prove that the factors of utilization of the Indrive application on online motorcycle taxis can affect the interest in use in its users. The number of respondents in this study were 150 respondents. The data analysis used the Structural Equation Modeling - Partial Least Square (PLS-SEM) analysis technique with the help of SmartPLS. The results of this study indicate that of the 8 hypotheses tested, 5 hypotheses were accepted and 3 hypotheses were rejected. The results of hypothesis testing state that the variables Performance expectancy, Effort expectancy, Facilitating condition Behavioural intention Price Value have a significant effect on usage behavior. As for the variable Social infuence Hedonic Motivation Habit on Use behavior, no significant effect was found.